Isosporosis Among Stray Pups - Seemanthini; k, Vinodkumar (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Canine isosporosis is an enteric disease caused by the genus Isospora characterised by severe colitis and enteritis. The present study involved 12 non-descript stray pups of 2-3 months age which had diarrhoea, anorexia, dullness and found positive for Isospora canis by floatation method. On physical examination, pale mucous membrane, sub-normal temperature and dehydration were noticed. Haematology revealed anaemia (reduced haemoglobin, total erythrocyte count and packed cell volume). Pups were treated with sulphonamide trimethoprim @ 15 mg/kg intravenously for 5 days along with fluid therapy and iron supplementation. Marked clinical improvement was noticed by five days. The haematological parameters showed significant improvement after treatment.